Pathogenicity and Growth Conditions Modulate Fonsecaea Extracellular Vesicles’ Ability to Interact With Macrophages - Lucas de Oliveira Las-Casas; Clara Luna Freitas Marina; Raffael Júnio Araújo de Castro; Luísa Coutinho Coelho; Sônia Nair Báo; G. Sybren de Hoog; G. Sybren de Hoog; Vânia Aparecida Vicente; Larissa Fernandes; Anamelia Lorenzetti Bocca (Frontiers in Cellular and Infection Microbiology, 2022)
Chromoblastomycosis (CBM) is a chronic cutaneous and subcutaneous mycosis caused by black, dimorphic, and filamentous fungi of the Herpothrichiellaceae family, such as species of the genus Fonsecaea. These fungi can switch between the saprophytic forms (conidia and hyphae) and the pathogenic form, the muriform cells (MCs), which is considered an essential mechanism for fungal virulence. Nearly all types of cells can produce membranous structures formed by a lipid bilayer that communicate extracellularly with other cells, known as “extracellular vesicles” (EVs), which may act as virulence factors, as observed for several species of pathogenic fungi. Our findings demonstrated for the first time that F. pedrosoi, F. nubica, and F. erecta produce EVs in response to nutritional conditions. The EVs varied in sterol and protein contents, size, and morphology. Moreover, the EVs induced different cytokine and nitric oxide release patterns by bone marrow-derived macrophages (BMDMs). The EVs activated IL-1β production, possibly acting as the first signal in inflammasome activation. Unlike the pathogenic species, the EVs isolated from F. erecta did not significantly stimulate TNF and IL-10 production in general. Overall, these results demonstrated that different species of Fonsecaea produce EVs capable of modulating pro- and anti-inflammatory cytokine and nitric oxide production by BMDMs and that growth conditions affected the immunomodulatory capacities of the EVs as well as their size, content, and morphology.